Voluntary disclosures and the stock price synchronicity - evidence from New Zealand - Tian, Enwei (Auckland University of Technology, 2014)
This paper investigates if there is a significant association between the informational opacity of the firm which is measured by voluntary disclosure levels, and the extent of firm-specific information incorporated into the share price as measured by synchronicity in New Zealand stock market. I apply three panel data regression analyses to a sample of 297 listed companies’ fiscal year observations over the 2001 to 2005 period. These three regressions are based on three different measurements of dependent variables but the same set of control and independent variables. The three dependent observations include one synchronicity risk measure and two idiosyncratic measures. My variable of interest in this study is a disclosure score which is a measurement of voluntary disclosures of firm specific information. I regress synchronicity on disclosure level to inspect whether the amount of disclosed firm information impounded on the share price is mirrored in stock price synchronous movement. The results imply that the level of firm’s voluntary disclosures reflects on the stock price synchronicity with the market and industry index. The paper finds that in New Zealand, firm disclosure levels are negatively associated with stock price synchronicity and positively related to idiosyncratic risk. This study also runs additional three regressions by controlling systematic risk in the original three models due to the limitation of synchronicity or idiosyncratic risk measurement according to Li et al. (2013). The new result also gives the same correlations among my test variables, and it further confirms that more voluntary disclosures of firm specific information will lighten the stock price co-movement. Moreover, I also test the validity of synchronicity measurement via earnings response coefficient model following Gul et al. (2010) study, and this new result verifies that my synchronicity measure is effective. Based on all regressions analyses, the results suggest that a high disclosure score (SDSCORE) is usually associated with a high idiosyncratic risk (ISR1 or ISR2) but a lower stock price synchronicity (SYNCH). The findings highlight the importance of voluntary disclosures which will promote transparency in the share market to decrease the share price synchronicity.
Keywords: Accounting; Voluntary disclosures; Stock price synchronicity; R-squared; ERC test; New Zealand